Percutaneous two unilateral iliosacral S1 screw fixation for pelvic ring injuries: a retrospective review of 38 patients - Whee Sung Son; Jae-Woo Cho; Nam-Ryeol Kim; Jun-Min Cho; Nak-Jun Choi; Jong-Keon Oh; HanJu Kim (Journal of Trauma and Injury)
Purpose Percutaneous iliosacral (IS) screw fixation for pelvic ring injuries is a minimally invasive technique that reduces the amount of blood loss and shortens the procedure time. Moreover, two unilateral IS S1 screws exhibit superior stability to a single IS screw and are also safer for neurological injuries than an S2 screw. Therefore, this study aimed to evaluate fixation using percutaneous two unilateral IS S1 screws for pelvic ring injuries and its subsequent clinical outcomes. Methods We retrospectively reviewed 38 patients who underwent percutaneous two unilateral IS S1 screw fixation for pelvic ring injuries. The procedure time, blood loss, achievement of bone union, radiological outcomes (Matta and Tornetta grade), and postoperative complications were evaluated. Results The mean procedure time, hemoglobin loss, bone union rate, and time to union were 40.1 minutes (range, 18–102 minutes), 0.6 g/dL (range, 0.3–1.0 g/dL), 100%, and 153.2 days (range, 61–327 days), respectively. The Matta and Tornetta grades were excellent, good, and fair in 24 (63.1%), 11 (28.9%), and three patients (7.9%), respectively, and the postoperative complications were S1 screw loosening, widening of the symphysis pubis (2.3 and 2.5 mm), lumbosacral plexopathy, and S1 radiculopathy in one (2.6%), two (5.3%), one (2.6%), and one patient (2.6%), respectively. However, all neurological complications recovered spontaneously. Conclusions Percutaneous two unilateral IS S1 screw fixation was useful for treating pelvic ring injuries. In particular, it involved a short procedure time with little blood loss and also led to 100% bone union and good radiological outcomes.